Persisting sicca complaints in sarcoidosis - Hofauer, Benedikt; Wiesner, Miriam; Zhu, Zhaojun; Stock, Konrad; Peltz, Friedhelm; Thuermel, Klaus; Strassen, Ulrich; Johnson, Felix; Knopf, Andreas (Frontiers in Medicine, 2022)
Background: Sarcoidosis is a systemic inflammatory disease that is characterized by non-casing granulomas. Besides the lung as classical site of affection, extrapulmonary manifestations are common, for example cervical lymph nodes or the salivary glands. The aim of this investigation is the analysis of the long-term course of glandular symptoms with a focus on persisting sicca symptoms. Material and methods: All patients with the diagnosis of sarcoidosis over a period of 20 years in the departments of otorhinolaryngology, nephrology and pneumology were identified. In addition to clinical examinations and functional evaluation of the salivary glands, a sonographic examination of the salivary glands was carried out. Results: A total of 76 patients were included in the study (age 35.1 ± 21.6 years). At baseline, 32 out of 76 patients were suffering from xerostomia, 36 from keratoconjunctivitis sicca. While other salivary gland symptoms, such as gland enlargement, pain or facial nerve impairment, dissolved during the further course of the disease, xerostomia was still present in 29 and keratoconjunctivitis sicca in 35 out of 76 patients at the time of follow-up (which took place on average after 88.2 months). Conclusion: Sicca symptoms persist in patients with the diagnosis of sarcoidosis, while other salivary gland symptoms completely dissolve during the further course of the disease. This development appears to be independent of the type of therapy and should be considered during the follow-up of these patients, since sicca symptoms can cause further ocular, oral and dental damage.